The Integration of Descendants of Migrants from Turkey in Stockholm: The TIES Study in Sweden - Westin, Charles (Amsterdam University Press, 2015)
This timely book presents the results of the Integration of the Second Generation in Europe survey that examines the experiences of residents of Stockholm who are descended from Turkish migrants